Atmospheric chemistry of nitrous acid and its effects on hydroxyl radical and ozone at the urban area of Beijing in early spring 2021. (1st January 2023) - Zhang, Wenqian; Tong, Shengrui; Lin, Deng; Li, Fangjie; Zhang, Xinran; Wang, Lili; Ji, Dongsheng; Tang, Guiqian; Liu, Zirui; Hu, Bo; Ge, Maofa
Abstract: The atmospheric chemistry of nitrous acid (HONO) has received extensive attention because of its significant contribution to hydroxyl (OH) radicals. Heterogeneous reaction of NO2 is an important HONO source, and its reaction mechanism is affected by many factors, such as concentration of gaseous NO2, surface adsorbed water, relative humidity and temperature. Although laboratory studies have confirmed the effect of temperature on heterogeneous reaction of NO2, there are few field observations reporting about it. We have conducted a field observation in the early spring 2021 when the temperature ranges widely (−0.1–24.7 °C). Concentrations of HONO and related pollutants at the urban area of Beijing are obtained. The hourly averaged HONO concentration reaches 4.87 ppb with a mean value of 1.48 ± 1.09 ppb. Combined with box model and RACM2 mechanism, we found an optimal temperature (∼10 °C) existing for heterogeneous reaction of NO2 during this measurement. When considering the promotion effect of optimal temperature, the contribution of heterogeneous reaction of NO2 to HONO can increase by 10%. This result will provide essential information for developing an accurate model of HONO chemistry in the atmosphere especially for certain periods or regions with temperature changing largely. Moreover, heterogeneous reaction of NO2 is the vital source of HONO, contributing 63–76% to simulated HONO during this measurement. Note that HONO photolysis is the most important formation pathway of OH radicals, and ambient HONO concentration is the obbligato constraint for evaluating atmospheric oxidation by model simulations. Graphical abstract: Image 1 Highlights: Hourly averaged HONO concentration reaches 4.87 ppb with a mean of 1.48 ± 1.09 ppb. An optimal temperature of ∼10 °C exists for heterogeneous reaction of NO2 . Heterogeneous reaction of NO2 contributes 63–76% to simulated HONO. HONO photolysis is the most important formation pathway of OH radicals.